The Relationship of Self-Confidence With Students' Science Learning Outcomes in Elementary Schools: Hubungan Sikap Percaya Diri Dengan Hasil Belajar IPA Siswa Di Sekolah Dasar - Pusfitasari, Rosi Anggraini; Wati, Tri Linggo (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of analyze the correlation between self-confidence with science learning outcomes for third grade students at SD Negeri 190 Gresik. This research is motivated by several obstacles faced in the science learning process, namely the majority of students have problems in the learning process, namely a lack of self-confidence. Lack of confidence in science subjects like this will have an impact on the success of students in achieving the desired learning outcomes. This type of research is correlation research. The data collection techniqu used is a self-confidence questionnaire towards science learning. The result of the study indicate thet there is a relantionship between self-confidence towards third grade students science learning outcomes at SD Negeri 190 Gresik with a fairly strong relationship.